2006
DOI: 10.1093/jn/136.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Improves after Treatment of Schistosoma japonicum-Infected Children and Adolescents

Abstract: Studies addressing the relation between chronic schistosomiasis japonica and nutritional status are limited. We conducted a longitudinal treatment-reinfection study in Leyte, the Philippines, among 477 Schistosoma japonicum-infected subjects aged 7-20 y, to evaluate changes in nutritional status after treatment with praziquantel. Stool, Tanner stage, anthropometric indices, and hemoglobin (Hb) were evaluated at baseline, 4 wk post-treatment, and every 3 mo for 18 mo. Height-for-age Z-score (HAZ) and BMI Z-scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 29 publications
2
49
0
Order By: Relevance
“…6,25 Infection-related AI has been strongly linked to the presence of subclinical infection, both for children with subclinical malaria in Cote d'Ivoire, 6 and for Philippine children having persistent or recurrent low-level Schistosoma japonicum infection after praziquantel therapy. 25,26 Our current study of the mechanisms of anemia associated with prevalence parasitic infections suggests that AI combined with true iron deficiency is the primary source of childhood anemia in this area of coastal Kenya.…”
Section: Discussionmentioning
confidence: 89%
“…6,25 Infection-related AI has been strongly linked to the presence of subclinical infection, both for children with subclinical malaria in Cote d'Ivoire, 6 and for Philippine children having persistent or recurrent low-level Schistosoma japonicum infection after praziquantel therapy. 25,26 Our current study of the mechanisms of anemia associated with prevalence parasitic infections suggests that AI combined with true iron deficiency is the primary source of childhood anemia in this area of coastal Kenya.…”
Section: Discussionmentioning
confidence: 89%
“…The odds of stunting was 5 times higher among the schoolchildren infected with A.lumbricoides [AOR (95% CI) = 5.0 (2.7, 9. [15,36] and intervention studies that showed improved growth performance after schoolchildren were treated with anthelminthic drugs [37][38][39][40]. Intestinal helminth infections could affect linear growth and nutritional status through several mechanisms including decline in food intake [39,41]; nutrient wastage from blood loss, malabsorption and diarrheal episodes [41,42]; and suppression of hormones required for bone growth like the growth hormone (GH) and insulin-like growth factor-1 (IGF-1) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although much of impaired early childhood development in sub-Saharan Africa has been ascribed to protein, calorie, and micronutrient deficiencies, it is becoming increasingly apparent that the process of chronic parasitic infection is associated with continuing inflammation that can limit childhood growth 6,7,37 and cause persistent or recurrent anemia of chronic inflammation. 18 Despite the difficulties in isolating individual causes of undernutrition and anemia in developing areas, we were able to show a clear association between infection and both anemia and undernutrition after adjusting for sex-specific effects and possible SES and environmental confounders.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Previous studies have examined the overlapping effects of infection by soil-transmitted helminths (STHs), including hookworm, Ascaris lumbricoides, and Trichuris trichiura, on these outcomes, and more recently, studies have examined the combined effects of STH with schistosomiasis. 3,7,8 The public health importance of chronic malnutrition and anemia is in their intrinsically disabling effects. Related manifestations can often include reduced global functioning, 9 decreased physical performance, 10,11 and impaired cognition, 2,12,13 resulting in decreased human capital among adults in affected populations 14,15 with a related loss in years of healthy life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation